A new species of the genus Xiaomyia Sæther & Wang (Diptera: Chironomidae) from West Bengal, India - Hui, Poulami; Mahato, Achintya; Hazra, Niladri (Zootaxa, 2026)
A new species of the genus Xiaomyia Sæther & Wang, 1993 is described and illustrated from West Bengal, India, based on adult males. This represents the first new species of Xiaomyia recorded from India. Diagnostic morphological characters of the adult male, including features of the hypopygium, wing venation, maxillary palps, and antennal ratios, are duly examined and compared with the previously described species. The generic diagnosis is substantially amended to reflect novel morphological characters revealed by the new species, necessitating an update of the criteria used for identification and differentiation within Xiaomyia. The new species X. acuminata sp. nov. differs from the only other member of Xiaomyia primarily by having a long, pointed anal point. Molecular barcoding of the new species is also provided; the species status of Xiaomyia acuminata is strongly supported by an integrative analysis of the molecular data, exhibiting a minimum interspecific Kimura 2-Parameter (K2P) distance of 12.59% from its only nearest congener. Discovery of the new species raises the number of species of this least speciose genus to two worldwide.